2010
DOI: 10.1590/s1678-77572010000300016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alveolar bone loss in healthy children treated at private pediatric dentistry clinics

Abstract: ObjectivesThe purpose of this study was to evaluate the prevalence of alveolar bone loss (BL) in healthy children treated at private pediatric dentistry clinics in Brasília, Brazil.Material and MethodsThe research included 7,436 sites present in 885 radiographs from 450 children. The BL prevalence was estimated by measuring the distance from the cementoenamel junction (CEJ) to alveolar bone crest (ABC). Data were divided in groups: (I) No BL: distance from CEJ to ABC is ≤2 mm; (II) questionable BL (QBL): dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, this is anticipated due to the exfoliation of primary teeth and eruption of permanent teeth happens between the two groups. In this study, the findings of first group (4 to 5 years old) is similar to other study where the results displayed that age had no effect on the distance CEJ-ABC in the primary teeth phase, between 2 and 5 years of age of Brazilian children only 31 . Also, the findings of second group (9 to 10 years old) were similar to other study where there was no difference among the four age groups (6-9 years) and its mean distances where becoming somewhat smaller with age, but there is no any relevance to this drop when measurements become beneath the threshold CEJ-ABC distance 25 .…”
Section: Abbreviation: Mesial Aspect (M) and Distal Aspect (D) Readinsupporting
confidence: 90%
“…However, this is anticipated due to the exfoliation of primary teeth and eruption of permanent teeth happens between the two groups. In this study, the findings of first group (4 to 5 years old) is similar to other study where the results displayed that age had no effect on the distance CEJ-ABC in the primary teeth phase, between 2 and 5 years of age of Brazilian children only 31 . Also, the findings of second group (9 to 10 years old) were similar to other study where there was no difference among the four age groups (6-9 years) and its mean distances where becoming somewhat smaller with age, but there is no any relevance to this drop when measurements become beneath the threshold CEJ-ABC distance 25 .…”
Section: Abbreviation: Mesial Aspect (M) and Distal Aspect (D) Readinsupporting
confidence: 90%
“…A radiographic‐based study, performed by Guimaraes et al. in 2‐ to 11‐year‐old children, found definite bone loss in fewer than 1% and questionable bone loss in approximately 10% of subjects. A retrospective longitudinal study based on bitewing radiograph examination of 3‐ to 10‐year‐old subjects with no obvious signs of periodontitis initially found that periodontal bone loss increased with age, and the presence of tooth surfaces with either caries or restorations increased the probability of bone loss .…”
Section: Periodontal Disease In Brazilmentioning
confidence: 98%
“…For example, in the study by Poletto and Junior, 59 one of the key review articles in the field, the authors concluded that the previous literature provided little conclusive scientific evidence, specifically in the Brazilian scientific literature, a context in which the prevalence of alveolar bone loss was also studied in children considered healthy and treated in private paediatric dentistry clinics. 60 Moreover, it is evident that this concept has dominated the literature since that year, constituting the most researched term in 2012 and 2019, which further indicates the relevance of the topic.…”
Section: Factors Associated With the Impact Of Scientific Outputmentioning
confidence: 99%